(untitled) - Bamforth, Charles W. (Oxford, 2005)
Contents of the book is guide for all food scientists, technologists and microbiologists in the food industry and academia, this book will be an important addition to all libraries in food companies, research establishments and universities where food studies, food science, food technology and microbiology are studied and taught
Vi sinh vật thực phẩm nâng cao,Kỹ thuật lên men thực phẩm,Lên men thực phẩm
Keywords: Food microbiology,Alchoholic beverages,Lên men,Thực phẩm vi trùng,Fermentation; Microbiology